Micro and Nano Fabrication Technology - Yan, Jiwang; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This volume focuses on the state-of-the-art micro/nanofabrication technologies for creating miniature structures with high precision. These multidisciplinary technologies include mechanical, electrical, optical, physical, and chemical methods, as well as hybrid processes, covering subtractive and additive material manufacturing, as well as net-shape manufacturing. The materials the volume deals with include metals, alloys, semiconductors, polymers, crystals, glass, ceramics, composites, and nanomaterials. The volume is composed of 30 chapters, which are grouped into five parts. Engaging with the latest research in the field, these chapters provide important perspectives on key topics, from process developments at the shop level to scientific investigations at the academic level, offering both experimental work and theoretical analysis. Moreover, the content of this volume is highly interdisciplinary in nature, with insights from not only manufacturing technology but also mechanical/material science, optics, physics, chemistry, and more.
Part 1 Cutting technology -- Chapter 1 Micro chiseling of retroreflective arrays -- Chapter 2 Micro milling for functional surface -- Chapter 3 Micro cylindrical turning of calcium fluoride -- Chapter 4 Nanogrooving by using multi-tip diamond tools -- Chapter 5 Elliptical vibration cutting for difficult-to-cut materials -- Chapter 6 Micro machining of roller mould for roll-to-roll manufacturing -- Chapter 7 Tool servo-driven diamond turning for structured surface -- Part 2 Abrasive/tip-based machining technology -- Chapter 8 Micro/nano texturing by ultrasonic assisted grinding -- Chapter 9 Precision grinding for functional micro-structured surface -- Chapter 10 Micro fluid jet polishing -- Chapter 11 Bonnet polishing of microstructured surface -- Chapter 12 Soft-brittle semiconductors polishing with environment-friendly slurries -- Chapter 13 Three-dimensional fabrication of micro/nanostructure using scanning probe lithography -- Part 3High-energy beam machining technology -- Chapter 14 Femtosecond laser direct writing -- Chapter 15 Laser patterning of metallic glass -- Chapter 16 Ion beam machining -- Chapter 17 Electron beam machining -- Chapter 18 Microfabrication by laser lithography combined with ion etching -- Part 4 Molding/forming/self-organization technology -- Chapter 19 Replication of Micro/Nanostructures -- Chapter 20 Precision Molding of Microstructures on Chalcogenide Glass for Infrared Optics -- Chapter 21 Press molding of hybrid Fresnel lenses for infrared applications -- Chapter 22 Microspring fabrication by anisotropic gelation -- Chapter 23 Fabrication of Metallic Nanodot Arrays -- Chapter 24 Surface micro/nano-structuring using Self-assembly of fine particles -- Part 5 Physical/chemical machining technology -- Chapter 25 Micro electrical discharge machining of hard brittle materials -- Chapter 26 Micro Electrochemical Machining -- Chapter 27 Catalytic AFM-based nanofabrication -- Chapter 28 3D Microfabrication using photocatalytic reaction -- Chapter 29 Silicon etching for multiple-height microstructures -- Chapter 30 Local wettability modification and its micro-fluidic system application.
Keywords: Microtechnology; Microelectromechanical systems; Nanotechnology; Medical sciences; Biomedical engineering; Microsystems and MEMS; Nanotechnology; Health Sciences; Biomedical Engineering and Bioengineering